Herbal Drugs: Ethnomedicine to Modern Medicine - K G Ramawat [ editor ] (Springer, 2009)
"This reference work covers for the first time the herbal drugs used in ethnomedicine and validated on modern scientific basis. In depth information prepared by experts traces the evolution of herbal drugs with civilization and their use as antioxidants, anticancerous, chemopreventors, memory enhancers, neuroprotective, immunomodulator, anti-inflammatory, and in stroke, cardiovascular disorders, erectile dysfunction; also covering safety issues and toxic effects. Many of our modern medicine have come from traditional use of plants such as Curcuma, Ginkgo, and Ginseng. Therefore, information on herbal drugs, from ethnomedicine to modern use, has been arranged based on their involvement in various ailments. This book offers researchers working on diverse aspects of medicinal plants a complete coverage of botany, ethnology, pharmacology, toxicology and medicinal properties of medicinal plants. It provides essential source material to all working in the fields of agriculture, botany, pharmacy, traditional systems of medicine and drug industry."